Pengaruh Konsep Diri dan Mata Kuliah Kewirausahaan Terhadap Minat Menjadi Enterpreneur Pada Mahasiswa Semester VII STMIK Budi Darma - Andayanny Andayanny (Jurnal Manajemen, Ekonomi, Keuangan dan Akuntansi, 2020)
This study aims to see how Self Concepts and Entrepreneurship courses affect students' interest in entrepreneurship among students of semester VII STMIK Budi Darma with a sample of 25 people and by using SPSS 20.00 obtained the results of the regression equation Y = 5.776 + 0.177 X1 + 0.714X2 + e. This shows that the Entrepreneurship Subject Variable is the most influential variable on the interest of STMIK Budi Darma students to become entrepreneurs.